2013
DOI: 10.3748/wjg.v19.i39.6568
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of gastric cancer in patients aged ≥ 70 years

Abstract: Age ≥ 70 years was an independent prognostic factor for gastric cancer after gastrectomy. D1 resection is appropriate and postoperative chemotherapy is possibly unnecessary for elderly patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 30 publications
3
78
1
1
Order By: Relevance
“…Although in last years literature reports many studies concerning oncologic gastric surgery in elderly patients, there is still no homogeneity in the definition of this subgroup, and an established cut-off age seems far to be determined: in facts, if some authors defined as elderly patients with more than 65 years (14), other authors reported thresholds of 70, 75 or 80 years (3,11,(15)(16)(17), so that it is not easy to compare results from different studies.…”
Section: Who Are Elderly Patients?mentioning
confidence: 99%
See 4 more Smart Citations
“…Although in last years literature reports many studies concerning oncologic gastric surgery in elderly patients, there is still no homogeneity in the definition of this subgroup, and an established cut-off age seems far to be determined: in facts, if some authors defined as elderly patients with more than 65 years (14), other authors reported thresholds of 70, 75 or 80 years (3,11,(15)(16)(17), so that it is not easy to compare results from different studies.…”
Section: Who Are Elderly Patients?mentioning
confidence: 99%
“…Many studies showed similar DSS rates when comparing the efficacy of D2 versus D1 in both young and elderly gastric cancer patients (3,11,16), although paradoxically a recent Italian RCT described a better DSS in patients aged ≥70 years after D1 lymphadenectomy (42).…”
Section: Extent Of Lymphadenectomy In Elderly Gastric Cancer Patientsmentioning
confidence: 99%
See 3 more Smart Citations